Cancer‐associated mutations in normal human endometrium: Surprise or expected?. Issue 10 (5th August 2020) - Kyo, Satoru; Sato, Seiya; Nakayama, Kentaro
Abstract: The human endometrium is an essential component in human reproduction that has the unique characteristic of undergoing cyclic regeneration during each menstrual cycle. Vigorous regeneration after shedding may be sustained by stem/progenitor cells, for which molecular markers have not been fully identified. Although clonality analysis using X chromosome inactivation patterns has shown that normal human endometrial glands are composed of a monoclonal cell population, whether clonal expansion is derived from stem/progenitor cells remains unclear. Remarkable advances in next‐generation sequencing technology over the past decade have enabled somatic mutations to be detected in not only cancers, but also normal solid tissues. Unexpectedly frequent cancer‐associated mutations have been detected in a variety of normal tissues, and recent studies have clarified the mutational landscape of normal human endometrium. In epithelial glandular cells, representative cancer‐associated mutations are frequently observed in an age‐dependent manner, presumably leading to growth advantage. However, the extremely high mutation loads attributed to DNA mismatch repair deficiency and POLE mutations, as well as structural and copy number alterations, are specific to endometrial cancer, not to normal epithelial cells. The malignant conversion of normal epithelial cells requires these additional genetic hits, which are presumably accumulated during aging, and may therefore be a rare life event. These discoveries could be expected to shed light on the physiology and pathogenesis of the human endometrium and urge caution against the application of genetic screening for the early detection of endometrial cancer. Abstract : Human endometrial gland exhibits clonal growth in each menstrual cycle possibly via stem/progenitor cells, with harboring frequent somatic gene mutations in cancer‐associated genes. These mutations may plays role in endometrial regeneration and pathogenesis of endometriosis or endometrial cancer.